2020
DOI: 10.21203/rs.3.rs-122187/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated Exosome-derived Mirnas Predict Osimertinib Resistance in Non-small Cell Lung Cancer

Abstract: Background: Non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations will inevitably develop drug resistance after being treated with the third-generation EGFR-tyrosine kinase inhibitor (TKI), osimertinib. In recent years, many studies have been focusing on the ability of exosomal miRNAs secreted by tumor cells to transmit resistance information. However, the mechanism of exosome-derived miRNAs in osimertinib resistance remains unexplored.Methods: We extracted and sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is possible that additional miRNAs contribute to osimertinib resistance as well. In a similar experimental setup, Li et al (32) reported miR-184 and miR-3913-5p to be upregulated in exosomes from osimertinib-resistant cells and in plasma. miR-184 did not reach the cutoff of 2-fold elevation in expression in any of our osimertinib-resistant lines and miR-3913-5p was not included in our NanoString analysis.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that additional miRNAs contribute to osimertinib resistance as well. In a similar experimental setup, Li et al (32) reported miR-184 and miR-3913-5p to be upregulated in exosomes from osimertinib-resistant cells and in plasma. miR-184 did not reach the cutoff of 2-fold elevation in expression in any of our osimertinib-resistant lines and miR-3913-5p was not included in our NanoString analysis.…”
Section: Discussionmentioning
confidence: 89%